Disparities in Physician-Patient Communication by Obesity Status. (26th November 2014) - Richard, Patrick; Ferguson, Christine; Lara, Anthony S.; Leonard, Jennifer; Younis, Mustafa
This study aimed to examine variations in patient-physician communication by obesity status. We pooled data from the 2005-2007 Medical Expenditure Panel Survey (MEPS), _included only individuals who completed the self-administered questionnaire themselves, and restricted the sample to patients who received care from primary care physicians. We included a total of 6, 628 unique individuals between the ages of 18 and 65 who had at least one office or hospital outpatient visit during the past 12 months. There are six outcomes of interest in this study. The patient-physician communication composite score is based on five questions that the MEPS adapted from the Consumer Assessment of Healthcare Providers and Systems Survey. The other five variables were: respect from providers, providers' listening skills, explanations from providers, time spent with patients, and patient involvement in treatment decisions. The key independent variable was obesity. Bivariate and multivariate models such as ordinary least squares (OLS) and logistic regression were used to examine the relationship between patient-physician communication and obesity status. Multivariate models showed that obese patients had a reduced physician-patient communication composite score of 0.19 (95% CI 0.03-0.34, p=0.02), physicians' show of respect OR 0.77 (95% CI 0.61-0.98, p=0.04), listening ability OR 0.82 (95% CI 0.65-1.02, p=0.07), and spending enough time OR 0.80 (95% CI 0.62-0.99, p=0.04) compared to non-obese patients. We found a negative association between physician-patient communication and patients' obesity status. These findings may inform public health practitioners in the design of effective initiatives that account for the needs and circumstances of obese individuals.